Antegrade cystoscopy - An innovative approach to managing acute urinary retention following vulvar reconstruction flap stenosis - Surbhi Agrawal; Caroline Brandon; Ghadir Salame (Elsevier, 2021)
Vulvar reconstruction can be performed following radical vulvectomy and is known to be associated with urologic complications. We describe the use of antegrade cystoscopy to manage acute urinary retention secondary to an obliterated urethral meatus following radical vulvectomy and reconstruction for radiation dermatitis. Antegrade cystoscopy was performed by applying the surgical concepts for suprapubic catheterization and general laparoscopy. Antegrade cystoscopy is a simple and safe approach for female patients with distorted pelvic anatomy from radical surgery and reconstructions for vulvar cancer.